A PATH ANALYTIC STUDY OF THE EFFECT OF BIG FIVE PERSONALITY TRAITS ON ASSERTIVENESS, BEING MEDIATED BY SELF-ESTEEM AND SOCIAL ANXIETY, AMONG UNDERGRADUATE STUDENTS OF MYANMAR INSTITUTE OF THEOLOGY - Myint, Naw Aye Thiri; Natalie Chantagul; Rajitha Menon (Scholar: Human Sciences, 2022)
The present study investigated the direct and indirect effect of big five personality traits on assertive communication among undergraduate students in Myanmar Institute of Theology (Liberal Arts Program), being mediated by self-esteem and social anxiety. This quantitative research employed path analysis using survey questionnaires with 156 undergraduate students whom age ranged from 21-29. The path analysis results indicated that students who have high scores in extraversion and neuroticism traits had both direct and indirect effects on their level of assertiveness, being mediated by self-esteem. Social anxiety could not predict the assertiveness in this study although it has direct negative association with extraversion.